Tinjauan Konstitusional terhadap Perpanjangan Program Sunset Policy - Rakhmindyarto, Rakhmindyarto (Jurnal Konstitusi, 2011)
This paper provides a constitutional review of the extension of the Sunset Policy program. It tries to analyze whether or not the extension of the Sunset Policy program abuses the existing law. The paper argues that even though the extension of the program does not break the Indonesian constitutional law, the government should be more prudent to establish  the next public policies based on the government regulation of the law substitute. This paper recommends to constituting a clear regulation in regard to the strict conditionals of the establishment of a government regulation of the law  substitute.